Prosedur pengembangan kurikulum (kajian literatur manajemen inovasi kurikulum) - Varary Mechwafanitiara Cantika (Inovasi Kurikulum, 2022)
The curriculum plays an essential role in educational success. Quality education starts with a suitable and appropriate curriculum. The curriculum is also a necessary component of education. The curriculum must be changed and updated to face the demands of the times to create superior graduates or Human Resources (HR) who can compete globally. This research aims to find out the various forms of curriculum development procedures. The research method used is a literature review from different trusted sources or previous research. The study results indicate that curriculum experts apply various curriculum development procedures. When viewed from the perspective of curriculum innovation management, the guidelines for curriculum development include curriculum supervision, curriculum organization, staffing, and curriculum planning. The existence of curriculum innovation management can be the answer to changes in the demands of the direction of education, which are influenced by various factors that are later expected to be able to provide new experiences to students.